Peran Kebudayaan India Pra-Buddha dalam Pembentukan Nilai Sosial Masyarakat Buddhis Awal - Meri Meri; Alfred Wijaya; Kabri Kabri; Partono Partono (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to analyze the formative influence of pre-Buddhist Indian culture on the development of social values within early Buddhist society. Prior to the emergence of Buddhism in the 6th century BCE, Indian civilization had already evolved a complex cultural and philosophical landscape characterized by the varṇa (caste) hierarchy, Vedic ritualism, and the metaphysical doctrines of the Upaniṣads concerning karma, saṃsāra, and mokṣa. Employing a qualitative library research method, this study draws on secondary historical and sociological literature as well as primary Buddhist scriptures from the Sutta Pitaka (Pali Text Society edition). The analysis identifies three major cultural elements Brahmanical ritualism, the doctrine of rebirth and moral causation, and the śramaṇa ascetic movements that provided both the context and the dialectical counterpoint to the rise of Buddhism. The findings reveal that the Buddha’s teaching emerged as a moral and philosophical critique of the Vedic worldview, rejecting hereditary privilege and ritual exclusivity in favor of ethical conduct (sīla), mental cultivation (bhāvanā), and compassionate social responsibility (mettā–karuṇā). Through this transformation, Buddhism redefined human worth based on moral action (kamma), rather than lineage or social status, thus creating an egalitarian and ethically grounded social order. Understanding the pre-Buddhist cultural background offers deeper insight into the sociological, philosophical, and ethical dimensions of early Buddhist thought and highlights its continuing relevance for contemporary discussions on social justice, equality, and interreligious harmony.